Organizational networks and sustainable urban water practices in US local governments. Issue 2 (22nd December 2021) - Pivo, Gary; Henry, Adam Douglas; Berger, Lena; Gomez-Fernandez, Edna Liliana
Abstract: Organizational networks are regarded as key in policy innovation for sustainable development. They are thought to enhance innovation through access to first-hand experience, enhanced trust within a community, and exposure to role models and competitors. Despite theoretical pertinence, organizational networks have not been studied as much as other drivers of innovation, such as organizational capacity, leadership, and the socio-political environment. This empirical study explores how networks affect the implementation of Sustainable Urban Water Management Practices (SUWM) at the local level. Using data from 110 local governments in five US regions, we examine the relationship between social interaction and the implementation of SUWM, and how this relationship depends on the types of interaction partners. Our findings show that local governments with larger organizational networks implement more SUWM practices. Collaboration with non-governmental organizations, particularly water sector associations, is strongly associated with an increase in use of SUWM practices. Overall, our findings suggest that creating and maintaining a robust organizational network of other government agencies and non-governmental organizations, especially water sector associations, increases the chances that a local government will implement more SUWM practices. HIGHLIGHTS: The use and consideration of sustainable urban water practices are statistically linked to local policy networks. Governments with larger policy networks implement more practices. Non-governmental organizations are key drivers of the use of sustainable practices. Change agents can promote change by involving local water agencies in networking opportunities with NGOs and other agencies.